A Translation Analysis Of Verb Phrase Found In Linguistics Across Cultures Into Linguistik Di Pelbagai Budaya - Rusetyawan, Ardhi; , Dr. Dwi Haryanti, M.Hum; , Drs. Sigit Haryanto, M.Hum (2014)
This research belongs to descriptive qualitative research. The research purposes to classify the translation variation of verb phrases and to describe the translation equivalence of the translation of verb phrases found in Linguistics Across Cultures and their translation. The data of this research are verb phrases in clauses, sentences, and their translation. The data source are "Linguistics Across Cultures" into "Linguistik di Pelbagai Budaya" book and informant. The writer uses documentation as the method of collecting data in this research. The writer uses data source triangulation by using documentation and combines documentation with open-questionnaires in the data validity. The results of the research shows that: first, there are 6 types of translation variation of verb phrases. They are: 1) 521 data or 73,25% belong to verb phrase is translated into verb, 2) 24 data or 3,35% belong to verb phrase is translated into noun, 3) 61 data or 8,50% belong to verb phrase is translated into adjective, 4) 1 datum or 0,25% belong to verb phrase is translated into adverb, 5) 5 data or 0,75% belong to verb phrase is translated into preposition, and 6) 99 data or 13,90% belong to verb phrase which is not translated. Second, there are 677 data or 95,20% belong to equivalent translation, and 34 data or 4,80% belong to non-equivalent translation.